Presence of a Global Language in India A Case for English - Khar, Meenakshi (JOURNAL OF INDIAN EDUCATION, 2013)
Societies have been losing out their native languages. As a result of vanishing of languages, many elements of traditional knowledge are also lost. The major reason of accelerated rate of the extinction of native languages is the forces of liberalisation and globalisation. Due to this English has acquired the status of language of opportunities and has endangered native languages. The paper will focus on the reasons of spread of English in our country where its growth is contrived and not organic. It is high time that educationists and linguists should develop meaningful and relevant curriculum of English so that it coexists with native languages.